Scientific expeditions in Tokugawa Japan: Historical background and results of official ventures to foreign lands - Švambarytė, Dalia (Acta Orientalia Vilnensia, 2008)
Vilnius University This article discusses the problem of the research expeditions to foreign lands during the period of national seclusion in Japan. Each historical period has its specific geographical perspective. The geographical thinking in Tokugawa Japan was influenced by a policy of self-isolation. In the Tokugawa period, Japan was more interested in protecting the boundaries than expanding its geographical horizons. There were, nevertheless, several expeditionary ventures launched by the government. This article presents the background of research expeditions dispatched by the shogunate and then moves to a discussion of the mechanism of these official expeditions and motivation behind them, as well as the nature of the political statements implied by the explorations and their results. The Japanese expeditions to the Pacific islands and northern region were mostly limited to scientific observation, mapping, and geographical survey, and the reasons for expeditionary ventures were security concerns rather than territorial expansion or the pursuit of economic interests. Although the links between the geographical exploration of the Tokugawa period and colonialism were weak, the expeditions had a considerable degree of political effect on the state policy of modern Japan.